Edukasi Pengenalan Minuman Herbal, Sebagai Minuman Kesehatan pada Masyarakat di Sekitaran Apotek Sari Mutiara - Manahan Situmorang; Devina Chandra; Dumartina Hutauruk; Theesyah R. Sianturi; Nurlaili Safitri; Widia Sari; Eva Diansari Marbun (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Traditional herbal drinks based on natural ingredients such as ginger, lemongrass, and lemon are widely known to have various health benefits. However, not all levels of society understand the properties, processing methods, and proper consumption of these herbal drinks. This community service activity aims to provide education regarding the benefits of herbal drinks to the community around the Sari Mutiara Pharmacy. The implementation method used was an interactive lecture, question and answer session, and distribution of information brochures. The results of the activity showed an increase in public understanding of the benefits and uses of herbal drinks. This activity was attended by 20 residents and is expected to be the first step in increasing awareness of consuming herbal drinks as a health promotion and prevention effort. Conclusion: Thecommunityserviceactivityto introduceherbaldrinks to the community around the Sari Mutiara Pharmacy successfully increased public understanding and interest in consuming herbal drinks as part of a healthy lifestyle.